Addressing Challenges in Language Learning and Innovative Solutions for Them - Kipchakova Sanobar Bahriddinovna; Esanova Farangiz; Sharifova Nozima (Zien Journals, 2024)
Language learning is a crucial aspect of human development, facilitating communication, cultural understanding, and professional growth. However, learners often encounter various challenges that hinder their progress. This scientific article explores the problems associated with language learning and presents innovative solutions to enhance the efficiency and effectiveness of language acquisition in a rapidly evolving globalized world.
Keywords: Technological gaps; access to language learning resources; retention